Clinical Features and Differential Diagnoses in Laryngeal Mucoepidermoid Carcinoma - Sepideh Mokhtari; Saeedeh Mokhtari (SAGE Publishing, 2012)
Mucoepidermoid carcinoma is the most common malignant tumor of salivary glands. However, it is a rare entity in larynx. Laryngeal cases are frequently misdiagnosed with other malignancies and they are under-reported. So, recognizing the clinical and histological features of this tumor is essential. Laryngeal mucoepidermoid carcinoma can arise in supraglottis, glottis and subglottis. Generally, it presents as a submucosal mass; therefore, progressive symptoms without any identifiable lesion in laryngoscopy must be well considered. The prognosis is somehow dependent on the histological features. In high-grade tumors, recurrence is more common and radical surgery with radiotherapy is recommended. In this paper, we provide a thorough literature review on mucoepidermoid carcinoma in the larynx. The most important distinguishing features of mucoepidermoid carcinoma and its two major differential diagnoses (squamous cell carcinoma and adenosquamous carcinoma) are clearly stated and pitfalls in true diagnosis of this tumor are discussed.